OPTIMALISASI PROFESIONALISME GURU MADRASAH IBTIDAIYYAH MELALUI PERAN KEPEMIMPINAN KEPALA MADRASAH - Muhtadin, Muhammad Akhsanul; Laksono, Tio Ari (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
Apart from being influenced by the effectiveness of teachers in the classroom, teaching standards and the completeness of facilities in schools are also influenced by the head of the madrasah. The implementation of education and teaching is greatly influenced by the leadership of the madrasa head, especially in fostering teacher professionalism in carrying out their duties. The teaching process in madrasas will be influenced by effective madrasah leadership. Qualitative literature reviews are part of this type of research. Then proceed with descriptive analysis, which involves data collection, organization, classification, and analysis, which are steps in the research process. To overcome the lack of professionalism of educational staff, the madrasa head has five functions, namely the madrasa head in the education management paradigm must at least be able to become an educator, manager, supervisor, leader, innovator, motivator.